Response distortion in personality measurement: born to deceive, yet capable of providing valid self-assessments? - Dilchert, Stephan; Ones, Deniz S.; Viswesvaran, Chockalingam; Deller, Jürgen (Psychology science, 2006)
This introductory article to the special issue of Psychology Science devoted to the subject of Considering Response Distortion in Personality Measurement for Industrial, Work and Organizational Psychology Research and Practiceʺ presents an overview of the issues of response distortion in personality measurement. It also provides a summary of the other articles published as part of this special issue addressing social desirability, impression management, self-presentation, response distortion, and faking in personality measurement in industrial, work, and organizational settings.